Maternal hypovitaminosis D presenting as late-onset hypocalcemic seizure in a term neonate: a case report - Achinta Kumar Mallick; Raj Kumar Yadav; Kiran Sannalli; Nitul Mohan Bewal (Egyptian Pediatric Association Gazette, 2023)
Abstract Background Vitamin D deficiency is a known morbidity among pregnant women. Maternal hypovitaminosis D results in poor fetal transplacental vitamin D accretion and decreased stores in the neonate. This in turn may lead to hypocalcemia in neonates, having presentations from being asymptomatic and tremors to hypocalcemic seizures. There are fewer case reports of hypocalcemic neonatal seizures as a result of maternal vitamin D deficiency. Case presentation A term male neonate developed multiple episodes of multifocal seizures on day six of life associated with hypocalcemia. He was also found to have hyperphosphatemia, raised alkaline phosphatase, and elevated parathormone levels with normal serum magnesium and renal function tests. Neonate and maternal serum vitamin D3 levels were also low. A diagnosis of late-onset hypocalcemic seizure secondary to maternal hypovitaminosis D was made and the baby made an uneventful recovery with parenteral calcium and oral vitamin D supplementation. On follow-up with therapy, the baby remained asymptomatic with normal serum calcium, phosphate, and vitamin D3 levels. Conclusion Hypovitaminosis D must also be considered as a contributing factor for late-onset hypocalcemic seizure in neonates.